Most frequent nursing diagnoses in elderly women hospitalized at the medical and surgical unit - Marin, M J; Barbosa, P M; Takitane, M T (Revista brasileira de enfermagem, 2000)
Due to the high incidence of elderly people which are presently hospitalized and the countless needs presented by them, this study aimed at describing the most common nursing diagnoses among fifty elderly hospitalized women, who were evaluated considering their need for home care. The authors concluded that the subjects studied presented diagnoses which involved all types of human response patterns, with particular emphasis on the diagnosis of knowledge deficit.